The effects of high temperature on blood serum parameters and the egg productivity characteristics of Japanese quails (Coturnix coturnix japonica) - Özbey, O.; Yildiz, N.; Aysöndü, M.H.; Özmen, Ö. (Asian Network for Scientific Information, 2004)
In this study, it was aimed to determine the effects of higher temperatures on the blood serum values, egg productivity, egg weight and the thickness of eggshell of the Japanese quails. By this purpose, two temperature groups were arranged by consisting of control (18-24°C) and trial (35°C) groups. In the end of the research, it was observed that the higher temperature increased some of the blood serum values such as glucose, Na, triglyceride (P<0.05), cholesterol (P<0.01) and uric acid (P<0.001) levels but reduced the blood serum protein (P<0.01), albumin (P<0.001), P (P<0.05), K (P<0.01) and ALP (P<0.05) levels. Even if the higher temperature has led a decrease in the egg productivity in all ages during the trial period, the difference that was observed in all ages except the seventh week was found important (P<0.05). The values of the egg weight in both control and trial groups were found as 10.53 and 9.93g (P<0.01); the values of eggshell thickness as 0.23 and 0.20 mm (P<0.001). © Asian Network for Scientific Information, 2004.
Keywords: Blood serum parameters; Egg characteristics; Quail; Temperature